2018
DOI: 10.3897/j.ruje.4.28482
|View full text |Cite
|
Sign up to set email alerts
|

The environmental Kuznets curve in the case of Russia

Abstract: This study explores the relationships between carbon emissions and their main determinants such as energy consumption, real income, international trade, level of education and level of urbanization in the Russian Federation, employing data for the period 1991–2016. Support for the environmental Kuznets curve hypothesis is found in this study, stating that environment pollution decreases in Russia after income achieves a certain threshold. The ARDL bounds test is employed in order to estimate short-run and long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 70 publications
5
21
1
Order By: Relevance
“…The results show that the sampled variables are cointegrated and the long-run relationship between the variables exists in the Russian case. The obtained results are in line with the results ofKetenci (2018).…”
supporting
confidence: 91%
See 1 more Smart Citation
“…The results show that the sampled variables are cointegrated and the long-run relationship between the variables exists in the Russian case. The obtained results are in line with the results ofKetenci (2018).…”
supporting
confidence: 91%
“…Given the heterogeneity of the obtained results on the EKC hypothesis, discussed in the previous section, we aim to fill the gap by enquiring into the nature of the relationship between CO 2 emission and agriculture as a share of GDP in the EKC framework. Following methodology for the Russian case, proposed by Ketenci (2018), the basic EKC hypothesis then can be presented as follows:…”
Section: Methodsmentioning
confidence: 99%
“…At the regional level, economic growth, energy intensity, energy structure, industrialization, and urbanization are found to affect CO2 emissions in the provinces of China for the period 1990-2014, based on quantile regression method (Xu, 2016). There are articles on the regions of Russia devoted to the determinants of CO2 emissions that have confirmed the EKC hypothesis (Ivanova, 2019;Ketenci, 2018;Mariev et al, 2020). Moreover, researchers found that modern technologies decrease CO2 emissions and mitigate emissions from energy consumption, while environmental policy is effective in decreasing CO2 emissions (Sohag et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…New technologies are found to decrease CO2 emissions; moreover, if urbanization is accompanied with new technologies, it is found to decrease CO2 emissions (Mariev et al, 2020). Energy consumption, real income, education, and urbanization are significant for CO2 emissions in the Russian regions (Ketenci, 2018). Regional environmental efficiency (the ratio of commodities not based on natural resources to labor, capital, natural resources expenditures and to environmental costs) has been growing since 2003 due to the development of the services sector of the economy and the progressive closure of traditional polluting enterprises.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Following the Kuznets model, the pattern of non-linear relationships Kuznet (1955) examined the impact of the growth of the economy on the disparity of income generated by the inverted U-shaped curve of Kuznets. The model also was developed the Kuznets curve with a distinct framework-like (Balaguer & Cantavella 2018;Ketenci 2018;Ridzuan 2019;Usman et al 2019) which examined the environmental Kuznets curve pattern relationship. This method was also used by (Bazillier & Sirven 2008) to evaluate the social Kuznets curve pattern relationship.…”
Section: Introductionmentioning
confidence: 99%